Association of urinary phthalate metabolites with all-cause and cardiovascular disease mortality among adults with diabetes mellitus: National Health and Nutrition Examination Survey 2005–2014 - Wang, Zhihong; Deng, Yao; Gao, Sikang; Lin, Zefang; Zheng, Zhixiong; Fang, Qin; Zhan, Meixiao; Sun, Taoping; Huang, Guomin; Geng, Xuyang (Frontiers in Public Health, 2023)
Background The study regarding phthalate metabolites and mortality among diabetes mellitus (DM) is limited. We aimed to examine the association of urinary phthalate metabolites with all-cause and cardiovascular disease (CVD) mortality among adults with DM. Methods This study included 8,931 adults from the National Health and Nutrition Examination Survey (NHANES) from 2005–2006 to 2013–2014. Mortality data were linked to National Death Index public access files through December 31, 2015. Cox proportional hazard models were used to estimate hazard ratios (HR) and 95% confidences (CIs) for mortality. Results We identified 1,603 adults with DM [mean ± SE age, 47.08 ± 0.30 years; 50.5% (833) were men]. Mono-(carboxynonyl) phthalate (MCNP), mono-2-ethyl-5-carboxypentyl phthalate (MECPP), and the sum of Di (2-ethylhexyl) phthalate (DEHP) metabolites (∑DEHP) were positively associated with DM (MCNP: OR = 1.53, 95%CI = 1.16–2.01; MECPP: OR = 1.17, 95% CI = 1.03–1.32; ∑DEHP: OR = 1.14, 95% CI = 1.00–1.29). Among DM patients, mono-(3-carboxypropyl) phthalate (MCPP) was associated with a 34% (HR 1.34, 95% CI 1.12–1.61) increased risk of all-cause mortality while the HRs (95%CI) of CVD mortality were 2.02 (1.13–3.64) for MCPP, 2.17 (1.26–3.75) for mono-(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP), 2.47 (1.43–4.28) for mono-(2-ethyl-5-oxohexyl) phthalate (MEOHP), 2.65 (1.51–4.63) for MECPP, and 2.56 (1.46–4.46) for ∑DEHP, respectively. Conclusion This study is an academic exploration of the association between urinary phthalate metabolites and mortality among adults with DM, suggesting that exposure to phthalates might be associated with an increased risk of all-cause and CVD mortality in DM. These findings suggest that patients with DM should carefully use plastics products.